2022
DOI: 10.3389/fphys.2022.1000593
|View full text |Cite
|
Sign up to set email alerts
|

Daytime napping, comorbidity profiles, and the risk of sarcopenia in older individuals

Abstract: Appropriate daytime napping is associated with the decreased risk of cerebro-cardiovascular diseases, but whether daytime napping affects sarcopenia remains to be explored. Our study plans to examine the associations between sarcopenia with daytime napping and comorbidity. The study population came from the China Health and Retirement Longitudinal Study 2011–2015. Latent class analysis (LCA) was used to identify comorbidity profiles based on 14 doctor-diagnosed chronic diseases. Subsequently, smooth function a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…In the current study, we discovered that midday nappers had a reduced risk of developing sarcopenia when compared to non-midday nappers. The result is in line with a recently published study that suggested that daytime napping is one of the important factors affecting the risk of sarcopenia in older people [38]. The possible mechanism of midday napping on sarcopenia can be addressed from the viewpoint of physical performance.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the current study, we discovered that midday nappers had a reduced risk of developing sarcopenia when compared to non-midday nappers. The result is in line with a recently published study that suggested that daytime napping is one of the important factors affecting the risk of sarcopenia in older people [38]. The possible mechanism of midday napping on sarcopenia can be addressed from the viewpoint of physical performance.…”
Section: Discussionsupporting
confidence: 89%
“…This study has multiple strengths. Compared to the closely related previous publications about nocturnal sleep duration and midday napping [8,9,21,38], the use of a prospective cohort design, which can suggest a causal relationship between sleep behavior and the incidence of sarcopenia, is a major strength of this study. Another strength is that this study used a large-scale representative population-based sample in China.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic conditions like hypertension and diabetes alter metabolism, affecting muscles. Abnormal sleep patterns disrupt recovery processes, while poor napping habits lower energy levels and hinder muscle recovery [ 49 , 50 ]. And sleep quality may also affect pain, a relevant variable in the association between depressive symptoms and sarcopenia [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, sarcopenia and osteoporosis, two degenerative diseases in the motor system of older adults, have attracted increasing attention from researchers due to increasingly aging societies ( Hu et al, 2022 ; Khosla et al, 2022 ). For instance, the proportion of the aged population in South Korea was 16.6% in 2021, and this may reach 25.5% after 10 years and 40.1% after 30 years ( Kwon et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%